THE ANALYSIS OF SPEECH FUNCTIONS USED BY AN ELESP LECTURER IN ENGLISH FOR YOUNG LEARNER CLASS - Yoannes Bosco Candrasuryya Mahendra; Felix Novaldy Zulham (English Language Education Study Program Association (ELESPA) or Asosiasi Program Studi Pendidikan Bahasa Inggris (APSPBI), Indonesia, 2017)
Speech function is a function performed by a speaker which has a purpose to specify their role. It is a situation where a speaker uses certain expression in order to convey some messages effectively. The use of speech function can be beneficial in our lives, especially in teaching learning processes. This research analyzed the speech function used by an English Language Education Study Program (ELESP) lecturer in English for Young Learners class. This study addressed one research question. It was the types of speech function which are used by an English Language Education Study Program of Sanata Dharma University lecturer in English for Young Learners class. The researcher used observation as the instrument to collect the data. Based on the findings, there were six speech functions used by the ELESP lecturer in teaching English for Young Learner class. They were referential function, emotive or expressive function, directive or conative function, phatic function, metalinguistic function, and poetic function. The result of the study revealed that the use of speech function in the classroom depends on the context and situation. Hence, it is not merely a meaningless function, yet it provides a bunch of advantageous for both lecturer and students.